Analysis of Tourist Visit Response to Yeh Pulu Relief - Susanti, Putu Herny; Sugiharni , Gusti Ayu Dessy (Sebatik, 2025)
Yeh Pulu Relief is one of the leading cultural and historical tourism destinations in Bali. They offer archaeological value and natural beauty. However, this tourism potential has not been optimal. This study aimed to analyze visitors' responses to the experience of visiting Yeh Pulu Relief, including the level of satisfaction, attraction factors, and obstacles. The research was a quantitative approach by distributing questionnaires to 100 domestic and foreign tourist respondents. It used descriptive analysis to interpret the data. The results of the study show that most tourists visit Yeh Pulu Relief for their interest in culture and history (60%), 30% for Recreation or Photography, while 10% come from recommendations or desire to explore unique destinations. The level of visitor satisfaction is high (85%), with aspects of cultural value and site authenticity being the determining factors. However, several respondents highlighted the limitations of supporting facilities such as toilets, rest areas, and inadequate information. Most tourists are satisfied with the uniqueness, natural atmosphere, and historical value. However, several aspects, such as supporting facilities, access to information, and promotion, are considered for improvement. Tourists also provide suggestions for improvement, including the addition of tour guides, increasing cleanliness, and developing infrastructure. Yeh Pulu Relief has potential as a cultural tourism destination but requires optimization in management and facilities to improve the quality of visits. These findings can be a reference for managers and local governments in developing sustainable tourism strategies. This study contributes to the development of heritage destination marketing strategies in Bali.